Young adults' adjustment to a recent diagnosis of multiple sclerosis: The role of identity satisfaction and self-efficacy. Issue 1 (January 2019) - Calandri, Emanuela; Graziano, Federica; Borghi, Martina; Bonino, Silvia
Abstract: Background: Although multiple sclerosis (MS) is often diagnosed during young adulthood (18–30 years), there is a lack of knowledge on the psychological adjustment to the illness among recently diagnosed young adult patients. Objective/hypothesis: The aims of the study were to describe the adjustment to MS (depression, positive and negative affect) in a group of young adult patients and to investigate the role of identity satisfaction and self-efficacy in MS on adjustment. We hypothesized that the relationship between identity satisfaction and adjustment was mediated by self-efficacy (goal setting and symptom management). Methods: The cross-sectional study involved 66 patients (63.6% women) with a mean age of 25.2 years ( SD = 3.4) who had been diagnosed for no more than three years. Patients completed measures of identity satisfaction (Identity Motives Scale), Self-efficacy in MS (SEMS), Depression (CESD-10), Positive and Negative Affect (PANAS). Data were analyzed through factorial ANOVAs and hierarchical regression analysis. Results: Thirty-eight percent of patients reported depressive symptoms and negative affect mean score was higher than in the general population. Higher identity satisfaction was directly related to lower depression. Self-efficacy in goal setting partially mediated the relationship between identity satisfaction and positive affect, whereas self-efficacy in symptom management totally mediated the effect of identity satisfaction on negative affect. All results were significant at p < 0.05. Conclusions: The results suggest the usefulness of addressing identity redefinition and self-efficacy in psychological interventions aimed at promoting young adults' adjustment to MS in an early phase of the illness.